Selective Reactions of Cutaneous and Muscle Afferent Neurons to Peripheral Nerve Transection in Rats - Hu, Ping (J Neurosci, 2003)
To determine whether peripheral nerve injury has similar effects on all functional types of afferent neuron, we retrogradely labeled populations of neurons projecting to skin and to muscle with FluoroGold and lesioned various peripheral nerves in the rat. Labeled neurons were counted after different periods and related to immunohistochemically identified ectopic terminals and satellite cells in lumbar dorsal root ganglia. After 10 weeks, 30% of cutaneous afferent somata labeled from transected sural nerves had disappeared but, if all other branches of the sciatic nerve had also been cut, 60% of cutaneous neurons were lost. Small-diameter sural neurons preferentially disappeared. In contrast, the number of muscle afferent somata was not affected by transection of various nerves. p75 was downregulated in axotomized cutaneous neurons but in not axotomized muscle neurons. Conversely, p75 was upregulated in satellite cells around cutaneous but not muscle neurons. Consistent with this, perineuronal rings containing tyrosine hydroxylase, calcitonin gene-related peptide, galanin, or synaptophysin were formed preferentially around cutaneous neurons. Selective lesions of predominantly cutaneous nerves triggered the formation of rings, but none were detected after selective lesions of muscle nerves. We conclude that cutaneous neurons are both more vulnerable and more associated with ectopic nerve terminals than muscle neurons in dorsal root ganglia after transection and ligation of peripheral nerves.